TBAI/TBHP-Mediated Cascade Cyclization toward Sulfonylated Indeno[1,2-c]quinolines - Jatuporn Meesin (2018)
© 2017 American Chemical Society. Treatment of ortho-amino-substituted aryldiyne derivatives with sulfonyl hydrazides in the presence of tetrabutylammonium iodide (TBAI) and tert-butyl hydroperoxide (TBHP) led to a cascade cyclization reaction to yield sulfonylated indeno[1,2-c]quinolines in moderate to good yields. The features of the methodology include metal-free reaction, the ease of reagent handling, and a broad functional group tolerance.